Exploring patterns of receipt of cash grants, health care, and education among 7–10 year old children in KwaZulu-Natal, South Africa. (July 2017) - Gordon, Nia; Godfrey, Erin; Aber, J. Lawrence; Richter, Linda; ,
Abstract: The South African government offers three main services to improve the developmental potential and overall well-being of the country's children: cash grants, health care, and education. There is research to suggest that receiving supports to the household in multiple domains simultaneously might improve children's development over and above improvements to development that are typically experienced when receiving a single developmental support, however, no research to date has empirically examined the patterns by which these services may be received, the associated quality of these services, the multilevel characteristics of children and their households that might predict receiving particular patterns of services, or the relationship between service receipt and children's academic and cognitive development in a natural (non-experimental) environment in South Africa. This paper uses three-step latent class analysis to explore patterns of receipt of the three primary government-provided services, the child-, caregiver-, household-, and community-level factors that predict receipt of these patterns, and the associations between service receipt patterns and the academic and cognitive outcomes of low-income 7–10 year old children living in peri-urban and rural regions of KwaZulu-Natal, South Africa, while accounting for potential sources of selection bias. Results revealed three service receipt patterns: primarily education, primarily cash grants and education, and all three services, showed that household level factors were most predictive of service receipt such that the most economically disadvantaged households were likely to receive the most services, and found that children receiving more services had poorer math outcomes as compared to children receiving fewer services. Highlights: Variation in patterns of services received among households suggests that there are gaps in service access and utilization. There is potential to improve the targeting of these services to marginally advantaged service-eligible households. Advantage may be conducive to math skills such that differential receipt of services is confounded with level of advantage.